An analysis of the anti-avoidance provision section 103 of the South African Income Tax Act 58 of 1962 - Mponco, Nelisa Phiwokazi (Centre for Law and Society, 2024)
"It is trite law that His Majesty's subjects are free if they can, to make their own arrangements so that their cases may fall outside the scope of the Taxing Acts. They incur no legal penalties and strictly speaking, no moral censure if, having considered the lines drawn by the legislature for the imposition of taxes, they make it their business to walk outside them."1 However, the South African Income Tax Act 58 of 1962 contains a general anti avoidance section, as well as specific anti avoidance sections. The legislature, having observed the growing industry of avoidance, enacted the law to counter tax avoidance. Therefore, the purpose of this dissertation is to analyse the law in guestion and see how the courts interpret the law in order to enforce anti tax avoidance provisions. To motivate this objective, this dissertation will be divided into three parts. Firstly, dealing with general anti-tax avoidance section 103, secondly, sections and finally, interpretation will be looked at. specific anti-avoidance of fiscal legislation will be looked at.